KEPEMIMPINAN TRANSFORMASIONAL CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI KANTOR KECAMATAN MANTIKULORE KOTA PALU - Karim, Fiqran Ramadan (Katalogis, 2018)
Transformational Leadership Camat in Improving Performance Employees Office in Mantikulore District Palu.As for the purpose of this research is to know the leadership of transformational camat in improving the performance of employee of Mantikulore District Office of Palu City. The main theory of transformational leadership Benard M. Bass is used as a reference that includes Attributed Charisma, Inspirational Motivation, Intellectual Simulation and Individualized Consideration. Research method used in this research is qualitative approach. The place of the research in the Camat office of Mantikulore Kota Palu with informants of seven people selected purposively. Technique of collecting data by observation, interview and documentation. By method of data analysis through data collection, data reduction, data presentation, and conclusion. Based on the results of research obtained, it can be concluded that the leadership of Camat transformational in improving the performance of employee offices Mantikulore District Palu City has not run well. When viewed from the four indicators of transformational leadership, one indicator of which is categorized quite well is: the attribute of charisma, the staff assume that the leader has a good leadership style should be a role model. It can be seen that the staff responded admiringly, respecting and believing the advantages possessed by a leader. meanwhile, three indicators, inspirational motivation, intellectual stimulation and individual consideration categorized as still less good, this is caused by: weak internal motivation owned by the sub-district that has not been able to inspire subordinates in the aspect of work until the fulfillment of all the goals of the organization; lack of skills in terms of staff knowledge and skills; lack of sub-district heads concerned the staff's needs for education and career development.